Numerical analysis of wall shear patterns on the external wall of an API 5L X42 natural gas pipe. (February 2015) - Mohsin, R.; Majid, Z.A.; Tan, F.L.
Highlights: Multiple failures of API 5L X42 pipe was studied using 3-D transient CFD. Standard k –epsilon model (SKE) of turbulent model was applied. Erosion pattern due to water and sand shear was determined. Different impaction angles produced different region of water and sand shear. Sand as the primary agent which causes pipe wall shear. Abstract: Natural gas pipeline is designed and constructed according to stringent international codes and standards, thus it hardly to rupture or leaks. However, erosive water jet from leaked water pipeline is able to erode the pipe surfaces and lead to its failure. Due to complications in understanding the subsurface hydrodynamics of buried pipe condition, Computational Fluid Dynamics (CFD) is commonly used to predict its characteristics to provide multifaceted overview of the erosion phenomenon. In this study, CFD simulation of multiple water leakage surface of 0.05 m diameter at 9 atm water pipeline pressure was performed with separation distance of 0.05 m, using standard k –epsilon model (SKE) of turbulent model. Simulation results were obtained using discrete random walk to determine the instantaneous fluid velocity. It was found that different region of water shear and sand shear on natural gas pipelines was formed due to the strikes of erosive slurry at different angles. The CFD simulation results showed that sand was the primary cause of the natural gas pipe wall shear, causing cutting and deformation region on the surface of gas pipe. The erosion pattern of the three ruptured holes from the incident sites had a similar trend with those from simulated CFD results of water jetting source at angles of 45°, 60°, and 75°.